The role of primary care professionals in maternal mental health - Flávia Ribeiro Rocha; Bruna Bosi de Oliveira Fernandes; Yan Victor Santana de Andrade; Alessandra da Rocha Arrais; Ângela Ferreira Barros (Universidade Federal do Ceará, 2024)
Objective: to analyze the actions of primary care professionals when faced with situations of psychological distress and/or psychosocial vulnerability among pregnant women and postpartum women. Methods: a descriptive and exploratory study was carried out with 78 health professionals working in the family health strategy, who were asked to complete a questionnaire on professional characterization and situational analysis. Results: most health professionals see pregnant /postpartum women daily (55.1%). For 66.7% of these professionals, they identify signs /symptoms of emotional, psychological, or mental distress in a minority of their visits to this public. Regarding the training of professionals to act and help pregnant /postpartum women concerning mental health, 76.9% have doubts, 89.7% have not participated in training on the subject, and all agreed with its relevance. The textual analysis of the discursive responses resulted in two categories: Qualified listening as a welcoming tool and shared care and referral to specialized professionals. Conclusion: family Health Strategy professionals reported doubts and weaknesses regarding managing the mental health of pregnant and postpartum women. Contributions to practice: these professionals experience situations that require them to deal with issues related to perinatal mental health and perceive training to meet this demand as relevant.